2016
DOI: 10.2459/jcm.0000000000000274
|View full text |Cite
|
Sign up to set email alerts
|

Documented atrial fibrillation recurrences after pulmonary vein isolation are associated with diminished quality of life

Abstract: In patients without documentation of atrial fibrillation, QoL increased up to the level of the general population after PVI, but it remained lower in patients with recurrences. In the latter group more ECGs were done, suggesting that QoL relates particularly to symptomatic episodes. Improvement of QoL is therefore an important attribute of PVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…We believe that rhythm monitoring is an important additional aspect in order to correctly understand the effects on PROs. Intermittent monitoring may have contributed to the conflicting results reported by these studies, with some reporting improvement in generic PROs regardless of AF recurrences and others improvement only in patients who are classified as free of AF recurrences . The recently published 5‐year follow‐up of MANTRA‐PAF (The Medical Antiarrhythmic Treatment or Radiofrequency Ablation in Paroxysmal Atrial Fibrillation) trial showed that the improvement in generic HRQoL measured by SF‐36 seen at 2 years after ablation remained and was similar in patients who underwent AF ablation and pharmacological rhythm control in spite of more AF recurrences in the latter group .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that rhythm monitoring is an important additional aspect in order to correctly understand the effects on PROs. Intermittent monitoring may have contributed to the conflicting results reported by these studies, with some reporting improvement in generic PROs regardless of AF recurrences and others improvement only in patients who are classified as free of AF recurrences . The recently published 5‐year follow‐up of MANTRA‐PAF (The Medical Antiarrhythmic Treatment or Radiofrequency Ablation in Paroxysmal Atrial Fibrillation) trial showed that the improvement in generic HRQoL measured by SF‐36 seen at 2 years after ablation remained and was similar in patients who underwent AF ablation and pharmacological rhythm control in spite of more AF recurrences in the latter group .…”
Section: Discussionmentioning
confidence: 99%
“…AF ablation has been shown to improve PROs in patients with AF, predominantly using generic instruments during intermittent rhythm monitoring . Occasionally, the resulting HRQoL was compared with that of the general population …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on QoL after catheter ablation demonstrated significant improvement after ablation, particularly in patients without AF recurrence. [16][17][18] Studies that compared catheter ablation with AAD therapy reported that QoL scores were significantly higher in patients who underwent catheter ablation than in patients with AAD treatment. [19][20][21] Small, nonrandomized studies have reported an improvement of QoL after thoracoscopic surgery for AF, similar to the change in QoL that was observed after catheter ablation.…”
Section: Quality Of Life After Atrial Fibrillation Ablationmentioning
confidence: 99%